Psychological Characteristics Of The Development Of Generosity In Children (Eurasian Scientific Herald, 2022)
Greed is far from being the most attractive human trait. Excessively greedy people are perceived by society as a rule negatively. Yes, and for them their greed can cause a lot of problems.